PENENTUAN OBJEK WISATA FAVORIT DI PULAU NUSA PENIDA MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING METHODE (SAW) - Ni Kadek Sukerti (LPPM STMIK El Rahma Yogyakarta, 2019)
The level of development of tourism in Klungkung especially in Nusa Penida has experienced a significant increase. This is inseparable from the smooth sea transportation in the form of speedboats with additional service schedules. The increase has also been influenced by the discovery of a number of new tourist attractions and maritime tours that are especially enjoyed by foreign tourists (diving and snorkeling). The location of the tourist attractions are not in one place but spread in several places with a considerable distance. If the vacation is only for one day, then the tourists must be able to choose attractions that line between the departing lane and the return lane so that it is more efficient. The data to be used in this study are internal and external data, alternatives that will be compared are a number of tourist sites with several criteria to be used. The method for processing data to be used is one of the methods in the Multi-Attribute Decision Making (MADM), the Simple Additive Weighting (SAW) Method. This method is used to find weighted sums and performance ratings on each alternative on all attributes. Research methods carried out starting from literature studies, interviews, data analysis to be used, data processing with the method of Simple Additive Weighting (SAW) method. The research is done in order to enable the tourists to determine the choice of tourist attractions that will be visited during their vacation on the island of Nusa Penida more easily. Based on the criteria and alternatives used, the study has resulted in having Cystal Bay as the most visited tourist attraction with a total preference value of 2.9200.